Long Non-Coding RNA CCAT2 Activates RAB14 and Acts as an Oncogene in Colorectal Cancer - Wang, Dalu; Li, Zhilong; Yin, Hongzhuan (Frontiers in Oncology, 2021)
Here, we investigated the clinicopathological and prognostic potential of the long noncoding RNA Colon Cancer-Associated Transcript 2 (CCAT2) in human colorectal cancer (CRC). We used qPCR to quantify CCAT2 levels in 44 pairs of CRC tissues and adjacent nontumor and healthy colon mucosa tissues, and in several CRC cell lines (SW620, SW480, HT-29, LOVO, HCT116 and DLD-1) and normal human colorectal epithelial cells (HFC). We assessed the effects of CCAT2 overexpression or knockdown on the proliferation, migration and invasion by SW620 and LOVO cells using CCK-8, transwell, and wound‑healing assays, respectively. We also investigated the potential interaction between CCAT2 and TAF15 through RNA pull down and rescue experiments. Lastly, we evaluated the expression of the cell cycle progression markers and GSK3β signaling pathway proteins using Western blotting. Our results showed that CCAT2 was upregulated in CRC tissues and cell lines as com-pared to controls. Ectopic expression of CCAT2 promoted CRC cell proliferation, migration and invasion, likely through direct interaction with TAF15, transcriptional activation of RAB14, and activation of the AKT/GSK3β signaling pathway. In vivo, CCAT2 promoted CRC cell growth and metastasis in nude mice. Taken together, these results highlight the actions of CCAT2 as a CRC oncogene.